2002
DOI: 10.1074/jbc.m200191200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mode of Interference with Nuclear Factor of Activated T-cells Regulation in T-cells by the Bacterial Metaboliten-Butyrate

Abstract: The transcription factor nuclear factor of activated T-cells (NF-AT) plays an essential role in the activation of many early immune response genes. A dynamic equilibrium between calcineurin and cellular kinases controls its phosphorylation and thus regulates its activity by determining its subcellular localization. Here, we demonstrate that T-cell activation in the presence of the bacterial metabolite n-butyrate, which leads to inhibition of interleukin-2 transcription, is characterized by the maintenance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…We examined the effect of butyrate on ERK, JNK and p38 and also on the NF-kB signalling pathways activated by LPS and Con A, since they have been described to be directly involved in the control of the expression of IL-8 in epithelial cells (Böcker et al, 2000), several cytokines in T-lymphocytes (Feske et al, 2001;Ortega-Pé rez et al, 2005;Paccani et al, 2002) and most of the inflammatory markers expressed in macrophages (Comalada et al, 2003a(Comalada et al, , 2003bXaus et al, 2000bXaus et al, , 2001. NFAT signalling pathway clearly participates in IL-2 production in lymphocytes, and it has been even described to be affected by butyrate in some studies (Diakos et al, 2002); however, we decided not to check this signalling pathway since its role in macrophages or epithelial cells, if any, is negligible (Comalada et al, 2006). Unfortunately, no modification on any of the tested signalling pathways was observed after butyrate treatment in macrophages and T-cells.…”
Section: Discussionmentioning
confidence: 95%
“…We examined the effect of butyrate on ERK, JNK and p38 and also on the NF-kB signalling pathways activated by LPS and Con A, since they have been described to be directly involved in the control of the expression of IL-8 in epithelial cells (Böcker et al, 2000), several cytokines in T-lymphocytes (Feske et al, 2001;Ortega-Pé rez et al, 2005;Paccani et al, 2002) and most of the inflammatory markers expressed in macrophages (Comalada et al, 2003a(Comalada et al, , 2003bXaus et al, 2000bXaus et al, , 2001. NFAT signalling pathway clearly participates in IL-2 production in lymphocytes, and it has been even described to be affected by butyrate in some studies (Diakos et al, 2002); however, we decided not to check this signalling pathway since its role in macrophages or epithelial cells, if any, is negligible (Comalada et al, 2006). Unfortunately, no modification on any of the tested signalling pathways was observed after butyrate treatment in macrophages and T-cells.…”
Section: Discussionmentioning
confidence: 95%
“…Translocation of NFATc1 to nuclei is regulated by Ca 2ϩ /calcineurindependent phosphatase pathway (47). Recently, it is shown that HDI NaB inhibited IL-2 transcription by affecting cellular localization of NFATc1 protein (48). Interestingly, it is reported that in addition to calcium-mediated signals, the TRAF6 and c-fos pathways were required in RANKL-induced NFATc1 expression (6).…”
Section: Discussionmentioning
confidence: 99%
“…Faust et al (2001) have argued that the anti-inflammatory actions of butyrate in the intestinal mucosa are unlikely to occur by direct regulation of cytokine-induced anti-inflammatory protein expression. Recent data from Diakos et al (2002) indicate that at relatively low concentrations (1 mM) butyrate inhibits production of the growth factor IL-2 (which is required for expansion of antigen-specific T cells) by decreasing nuclear binding of the transcription factor nuclear factor of activated T cells in both Jurkat cells and in primary T cells.…”
Section: Anti-inflammatory Actionsmentioning
confidence: 99%